Molecular Characterization and Expression Profiling of NAC Transcription Factors in Brachypodium distachyon L - Zhu, Gengrui (PLoS One, 2015)
NAC (NAM, ATAF1/2, CUC2) transcription factors are involved in regulating plant developmental processes and response to environmental stresses. Brachypodium distachyon is an emerging model system for cereals, temperate grasses and biofuel crops. In this study, a comprehensive investigation of the molecular characterizations, phylogenetics and expression profiles under various abiotic stresses of the NAC gene family in Brachypodium distachyon was performed. In total, 118 BNAC genes in B. distachyon were identified, of which 22 (18.64%) were tandemly duplicated and segmentally duplicated, respectively. The Bayesian phylogenetic inference using Markov Chain Monte Carlo (MCMC) algorithms showed that they were divided into two clades and fourteen subfamilies, supported by similar motif compositions within one subfamily. Some critical amino acids detected using DIVERGE v3.0 might contribute to functional divergence among subfamilies. The different exon-intron organizations among subfamilies revealed structural differentiation. Promoter sequence predictions showed that the BNAC genes were involved in various developmental processes and diverse stress responses. Three NAC domain-encoding genes (BNAC012, BNAC078 and BNAC108), orthologous of NAC1, were targeted by five miRNA164 (Bdi-miR164a-c, e, f), suggesting that they might function in lateral organ enlargement, floral development and the responses to abiotic stress. Eleven (~9.32%) BNAC proteins containing α-helical transmembrane motifs were identified. 23 representative BNAC genes were analyzed by quantitative real-time PCR, showing different expression patterns under various abiotic stresses, of which 18, 17 and 11 genes were up-regulated significantly under drought, H(2)O(2) and salt stresses, respectively. Only four and two genes were up-regulated under cold and cadmium stresses, respectively. Dynamic transcriptional expression analysis revealed that six genes showed constitutive expression and period-specific expression. The current results provide novel insights into the structure and function of the plant NAC gene family.